목표농도주입법에서 프로포폴 농도를 잘못 설정 후 교정 방법 - Lee, Won Il (The Graduate School, Ajou University, 2015)
Background: We investigated the correction methods following wrong-settings of emulsion concentrations of propofol as a countermeasure against erroneous target-controlled infusions (TCI). Methods: TCIs were started with targeting 4.0 μg/ml of effect-site concentration (Ceff) of propofol, and the emulsion concentrations were selected for 2.0% instead of 1.0% (FALSE1- 2, n = 24), or 1.0% instead of 2.0% (FALSE2-1, n = 24). These wrong TCIs were corrected at 3 min after infusion start. During FALSE1-2, the deficit was filled up while injecting after equilibrium (n = 12), or while overriding (n = 12). During FALSE2-1, the overdose was evacuated while targeting Ceff (n = 12) or targeting plasma concentration (Cp) (n = 12). The gravimetrical measurements of TCI reproduced the Cp and Ceff using simulations. The reproduced Ceff at 3 min (Ceff-3min) and the time to be normalized within ± 5% of target Ceff (T±5%), were compared between the correction methods. Results: During the wrong TCI, Ceff-3min was 1.98 ± 0.01 μg/ml in FALSE1-2, and 7.99 ± 0.05 μg/ml in FALSE2-1. In FALSE1-2, T±5% was significantly shorter when corrected while overriding (3.9 ± 0.25 min), than corrected after equilibrium (6.9 ± 0.05 min) (P < 0.001). In FALSE2-1, T±5% was significantly shorter during targeting Cp (3.6 ± 0.04 min) than targeting Ceff (6.7 ± 0.15 min) (P < 0.001). Conclusions: The correction methods, based on the pharmacokinetic and pharmacodynamic characteristics, could effectively and rapidly normalize the wrong TCI following erroneously selections of the emulsion concentration of propofol.
학위논문(석사)--아주대학교 일반대학원 :의학과,2015. 2
Keywords: 약물 전달 시스템; 주입 펌프; 정맥 주입; propofol; drug delivery systems; infusion pumps; intravenous infusion